Inclusive Reminders for Marketeers. (Hove : Inclusified, 2022)
Een set van 30 kaarten met essentiële geheugensteuntjes om marketeers en communicatieprofessionals alert te houden en hen te laten nadenken over hun rol als marketeer in de snel veranderende wereld van vandaag. / Inclusive Reminders for Marketeers is a tool for marketeers that want to move forward in a diverse society. It consists of 30 cards with essential reminders to keep you alert and make you reflect about your role as a marketeer in today’s fast-changing world.
Keywords: Vrije tijd : spelen